A simple and mild synthesis of a 4,5-cyclopropanated carbohydrate - Testero, Sebastian Andres (2006)
The synthesis of a 4,5-cyclopropanated carbohydrate was achieved in five steps from methyl α-d-mannopyranoside under mild conditions that avoid the use of carbene chemistry.